Racial Differences in Hypercholesterolemia Prevalence: : A Cross-sectional Study Using 2017-2018 National Health and Nutrition Examination Survey Data (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.
Keywords: Internal Medicine; Research